Pathological Features of Persistent Atrial Standstill Syndrome in Three Dogs. (October 2020) - Imai, Tomoko; Ojiro, Ryota; Kimura, Yusuke; Machida, Noboru
Summary: The hearts of three dogs, clinically diagnosed as having persistent atrial standstill syndrome (PAS), were studied post mortem . The most significant gross findings in the hearts of all three dogs were dilatation and marked reduction in the thickness of both atrial walls. Histopathologically, all three had widespread progressive loss of the atrial myocardium with replacement by fatty or fibrofatty tissue, consistent with atrial myopathy. The lesion mainly affected the upper half of both atria and was more severe in the epimyocardium and midmyocardium than in the endomyocardium. On the basis of these observations, it is proposed that the atrial myopathy commences in the upper regions of both atria and progresses downwards, as has been demonstrated electrophysiologically in PAS in humans, and extends from the epicardium towards the endocardium.